2002
DOI: 10.1007/s10350-004-6386-7
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Wall Recurrences After Colorectal Resection for Cancer

Abstract: The results of the Italian prospective Registry of Laparoscopic Colorectal Surgery confirm that the incidence of abdominal wall recurrences is similar to that reported in open studies (<1 percent). Most abdominal wall recurrences occurred in the learning curve period, suggesting that surgical experience may play a role in the development of this outcome. The prognosis of these patients is very poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The difference was not statistically significant. Silecchia et al [14] studied statistics of laparoscopic colorectal carcinoma in the Italian laparoscopic centre for nearly 5 years and found the rate of post-operative incision implantation was 0%–0.2%. Compared with open operation, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The difference was not statistically significant. Silecchia et al [14] studied statistics of laparoscopic colorectal carcinoma in the Italian laparoscopic centre for nearly 5 years and found the rate of post-operative incision implantation was 0%–0.2%. Compared with open operation, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the time of intestinal function recovery in the NOSE group was shorter than the traditional laparoscopic group. Tumor metastasis at the puncture and incision sites after laparoscopic surgery for colorectal cancer is still a controversial issue [15][16][17][18][19] . Because there is no auxiliary incision on the abdominal wall in NOSE surgery, there is no chance of incision metastasis [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies showed that the outcomes of laparoscopic and open colon surgery were similar [6,[7][8][9][10] , similar comparative outcomes have not been clearly demonstrated in laparoscopic rectal surgery. Concerns regarding laparoscopic rectal surgery are port-site and abdominal wall metastases and local oncological clearance [11][12][13][14][15] . In addition, laparoscopic rectal surgery has a challenging learning curve because of the deep and narrow pelvis and its assist-dependent procedure [16] .…”
Section: Introductionmentioning
confidence: 99%